A Confessional and Narrative Vision for Philosophy of Education: Justification and Basic Presuppositions of a Postmodern Approach. Issue 4 (8th August 2019) - Braun, Guilherme Junior; Potgieter, Ferdinand Jacobus
Abstract: In this article, we attempt to justify and present the basic presuppositions of a (Christian) confessional and narrative vision for philosophy of education in a postmodern context. We argue that although the nihilistic strand of postmodernity challenges the viability of religious discourse, postmodernity also re-opens the world toward its pre-rational foundations by means of the rediscovery of the primacy of narrative. In a postmodern age, any philosophy of education implies a basic understanding of, at least, the (historical) present and the past, in order to establish its place in the scholarly community of educators and educationists. We discern between two different versions of postmodernity and then proceed to explore what constitutes the postmodern narrative identity. Because the rise of postmodernity is intrinsically linked both to modernity and to the pre-modern Christian vision of the world, we explore the justification of a (Christian) confessional and narrative vision for philosophy of education in this respect by means of three fundamental questions. By elaborating on a postmodern Christian vision and by attempting to answer these questions in a narrative manner, we propose that a confessional and narrative vision for philosophy of education may be justified for the contemporary age. Toward this end, we deepen the postmodern rediscovery of narrative further by exploring the work of narrative. We then present a brief confessional account of the nature and scope of philosophy of education. Finally, we propose some of the central tenets of the Christian faith as presuppositions of our vision for philosophy of education.